Towards Tramway Safety by Managing Advanced Driver Assistance Systems depending on Grades of Automation ⁎This work has been funded by the Project: ELSAT 2020 by CISIT / GS2RI: Greener & Safer Rail Road Interaction. Issue 2 (2021) - Habib, Lydia; Oukacha, Ouazna; Enjalbert, Simon
Abstract: This paper presents a preliminary study for the assessment of tram safety by managing Advanced Driver Assistance Systems depending on the Grades of Automation. The Grades/Levels of Automation in automotive, aeronautics, maritime and railway systems are presented and compared with each other. Then, according to especially the implication level of a haptic system in each tram driving task, Grades of Automation for trams are proposed. In addition to the haptic system, a visual one that uses a Head-Up Display is defined. These systems are designed to help the tram driver cope with potential hazards by having a defensive driving. Therefore, the proposed Grades of Automation and the driver assistance systems are used in order to propose an experimental method to explore how this automation can affect the tram driver performance and the Human-Machine System safety.